2022
DOI: 10.14202/vetworld.2022.998-1005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a probiotic containing lactobacilli and bifidobacteria on the metabolic processes, litter microbiocenosis, and production indicators of broiler Pekin ducklings

Abstract: Background and Aim: The use of antibiotics is prohibited in poultry feeding in many countries worldwide, which has resulted in the emergence of antibiotic-resistant bacteria. Therefore, probiotic supplements are a good alternative in these circumstances. Probiotics, including Bifidobacterium adolescentis and Lactobacillus acidophilus, can reduce the development of resistance and stimulate the growth of broiler ducklings. This study aimed to evaluate properties of the probiotic supplement containing these bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…At the age of 62 days in the I experimental group, the differences with the control were 13.2% (p<0.001), and in the II experimental group -1.6%. (Khabirov et al, 2020(Khabirov et al, , 2021(Khabirov et al, , 2022.…”
Section: Resultsmentioning
confidence: 99%
“…At the age of 62 days in the I experimental group, the differences with the control were 13.2% (p<0.001), and in the II experimental group -1.6%. (Khabirov et al, 2020(Khabirov et al, , 2021(Khabirov et al, , 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Feed is the largest duck production cost; meeting feed requirements is important for successful duck farming. One study revealed that an increase in the digestibility of feed components and an improvement in feed conversion are the primary effects of probiotic supplements [ 23 ]. In this experiment, the live BW (days 85 and 125) and the ADG (28–85 d, 85–125 d, and 1–125 d) of the CP group were significantly higher than those of the Ctrl group.…”
Section: Discussionmentioning
confidence: 99%
“…Feed supplemented with Lactobacilli and Bifidobacteria stimulated the protein metabolism [ 23 ]. Additionally, the TP and albumin levels in the blood serum of 42-day-old ducklings fed probiotic-supplemented feed increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…A range of probiotic effects of Bifidobacterium sp. in poultry have also been reported in numerous in vitro and in vivo studies [21,22], including in broilers challenged with C. perfringens or with Salmonella typhimurium [23,24]. The reported effects range from improved weight gain and other growth indicators, to pathogen exclusion, to increased production of inflammatory cytokines and certain blood serum parameters.…”
Section: Introductionmentioning
confidence: 86%